2007
DOI: 10.1016/j.jenvman.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Financing electronic waste recycling Californian households’ willingness to pay advanced recycling fees

Abstract: The growth of electronic waste (e-waste) is of increasing concern because of its toxic content and low recycling rates. The e-waste recycling infrastructure needs to be developed, yet little is known about people's willingness to fund its expansion. This paper examines this issue based on a 2004 mail survey of California households. Using an ordered logit model, we find that age, income, beliefs about government and business roles, proximity to existing recycling facilities, community density, education, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 52 publications
(56 reference statements)
2
40
1
Order By: Relevance
“…the EU's Waste Electrical and Electronic Equipment (WEEE) and Reduction of Hazardous Substances Directive (RoHS) (see Europa, 2007), which seeks to minimize the environmental impact of e-scrap by holding producers responsible for financing collection, processing, and recovery. The state of California's recent legislation (IWMB, 2003;Nixon and Saphores, 2007) initially assigns an advanced recycling fee (ARF) of $6e$10 on all electronic products containing hazardous materials and the ARF is used to fund an electronics recycling system (Gable and Shireman, 2001) to compensate the processing costs incurred. In January 2009 the California ARF was increased to $8e$25 depending on screen size of the video display (SBOE, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…the EU's Waste Electrical and Electronic Equipment (WEEE) and Reduction of Hazardous Substances Directive (RoHS) (see Europa, 2007), which seeks to minimize the environmental impact of e-scrap by holding producers responsible for financing collection, processing, and recovery. The state of California's recent legislation (IWMB, 2003;Nixon and Saphores, 2007) initially assigns an advanced recycling fee (ARF) of $6e$10 on all electronic products containing hazardous materials and the ARF is used to fund an electronics recycling system (Gable and Shireman, 2001) to compensate the processing costs incurred. In January 2009 the California ARF was increased to $8e$25 depending on screen size of the video display (SBOE, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to the U.S. Census Bureau [12], individuals with less formal education and persons over 55 years are less likely to have Internet access. Generally, studies have found age, political ideology, and education correlated to increased recycling [13][14][15]. Consequently, given the subject matter and demographics, the study results should be viewed as an upper-bound estimate of recycling knowledge and actions.…”
Section: Study Resultsmentioning
confidence: 92%
“…Pate and Loomis (1997) found those that were older would be less willing to pay for programs to reduce environmental issues in San Joaquin Valley in California. Moreover, Nixon and Saphores (2007) found older adults were less likely to indicate support for advanced recycling programs, and numerous more studies have yielded similar results.…”
Section: Homeowner Participation Barriersmentioning
confidence: 89%